Prospek Penggunaan Isolat FMA Lokal di Lahan Pasang Surut Untuk Meningkatkan Produktivitas Kedelai - Ridwan Muis (Universitas Batanghari Jambi, 2021)
Tidal field has physical and chemical problems of land for the development of complex food crops including waterlogging and land physical conditions, soil acidity and organic acids on high peatlands, containing toxic substances and salt water intrusion, low natural soil fertility and diversity of land conditions. The continuous use of inorganic fertilizers apart from requiring high costs, also has the opportunity to destroy the balance of the environment. The use of local AMF isolates for efficient use of P fertilizers and increasing soybean productivity is interesting to consider, because it is an environmentally friendly activity